Collaborative Approaches to Enhancing Maternity Care: Interdisciplinary Management of Common and Emerging Critical Health Issues - Imran, Mohd (Asian Journal of Pharmaceutics (AJP), 2025)
Most of us would agree with the statement that pregnancy and childbirth are some of the most vulnerable phases in a woman’s life and women’s safety and maternity care heavily affects the maternal mortality rate and neonatal mortality rate. A well-developed caregiving system can help mother’s combat challenges, such as pre-eclampsia, gestational diabetes, and the safety of medication during breastfeeding. The analysis of this study focused on the participation of healthcare professionals, including doctors, midwives, nurses, and pharmacists, with the use of technologies, such as telemedicine, and centralized communication platforms. These include role ambiguity, communication challenges, and cultural hierarchies. Interdisciplinary approaches to delivery improved maternal care. Reduced complications and better patient outcomes ensued. Centralized systems eradicated errors, while good teamwork resolved issues with safety concerning maternal immunization and breastfeeding. Professional hierarchies and workload pressures were still problems. Nurses and pharmacists played key roles in mitigating medication-related risks. Communication frameworks and mutual respect also fostered collaboration. Role definition, training programs together, and an equitable distribution of workload must be present to overcome the barriers. Interdisciplinary collaboration is important for holistic maternity care. Empowerment of the health teams by technology, training, and streamlining will help improve maternal outcomes sustainably.